2022
DOI: 10.1371/journal.pcbi.1010264
|View full text |Cite
|
Sign up to set email alerts
|

Model-based translation of DNA damage signaling dynamics across cell types

Abstract: Interindividual variability in DNA damage response (DDR) dynamics may evoke differences in susceptibility to cancer. However, pathway dynamics are often studied in cell lines as alternative to primary cells, disregarding variability. To compare DDR dynamics in the cell line HepG2 with primary human hepatocytes (PHHs), we developed a HepG2-based computational model that describes the dynamics of DDR regulator p53 and targets MDM2, p21 and BTG2. We used this model to generate simulations of virtual PHHs and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…1b ), and subsequent activation of the DNA damage response were established by modifying existing models (Supplementary Fig. 1 ) 58 , 68 and applying them to individual hepatocytes, while accounting for the zonal differences in GSH and cytochrome P450 concentrations.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1b ), and subsequent activation of the DNA damage response were established by modifying existing models (Supplementary Fig. 1 ) 58 , 68 and applying them to individual hepatocytes, while accounting for the zonal differences in GSH and cytochrome P450 concentrations.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Because p53 induces the expression of p21, p53 influences the likelihood of senescence and proliferation events during regeneration. Previously, we suggested that the feedback strength of MDM2 on p53 could vary among cell types and play a role in interindividual variability 68 . Therefore, we decreased and increased the MDM2 feedback on p53 and phospho-p53 with a factor 10 and 100 and examined the effect of an APAP insult on p21, senescence and recovery from damage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations